1999
DOI: 10.1002/(sici)1099-0755(199901/02)9:1<141::aid-aqc328>3.0.co;2-c
|View full text |Cite
|
Sign up to set email alerts
|

A catchment-scale approach to the physical restoration of lowland UK rivers

Abstract: 1. This paper advocates a catchment‐scale perspective for river restoration and for individual rehabilitation works even though, at present, such works are often small‐scale and ad hoc in nature. The catchment‐scale approach is the logical consequence of the application of fundamental principles of river science to the philosophy of river restoration. 2. The five principles that river restoration should incorporate are: i) the hierarchy of river systems; ii) the proportional relationships between discharge and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(26 citation statements)
references
References 31 publications
0
26
0
Order By: Relevance
“…from headwaters to the mouth of rivers) as well as transverse structures (i.e. the cross section of the flood plain), whose functions and effects to ecological processes vary considerably (Harper et al, 1999;Boon, 1998). Thus, buffering was used in the absence of a more reliable and less complicated mapping technique for the riparian zones.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…from headwaters to the mouth of rivers) as well as transverse structures (i.e. the cross section of the flood plain), whose functions and effects to ecological processes vary considerably (Harper et al, 1999;Boon, 1998). Thus, buffering was used in the absence of a more reliable and less complicated mapping technique for the riparian zones.…”
Section: Discussionmentioning
confidence: 99%
“…If left unabated, the continuous misuse of these resources could bring further ecological problems and economic losses. Hence, there is a need to effectively manage these areas through restoration, rehabilitation, conservation or preservation programmes (Schiemer et al, 1999;Cals et al, 1998;Harper et al, 1999;Piegay and Landon, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…Including trees in buffers can influence shallow groundwater flow through increased transpiration, even in temperate climates (Komor and Magner 1996;Wagner and Bretschko 2003). Also riparian trees help reduce or denitrify groundwater nitrate (Haycock and Pinay 1993), and provide a range of benefits to aquatic ecosystems (Harper et al 1999). Studies on environmental effects of harvesting trees in riparian buffers are also published (Hubbard and Lowrance 1997;Liquori 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Restoration techniques are often directed towards the reestablishment of natural physical environment, including the riparian gallery (Harper et al 1999;Naiman and Décamps 1997;Piégay and Landon 1997). Many authors have demonstrated significant improvements in water quality and aquatic communities (Lazdinis and Angelstam 2005;Thoms and Sheldon 2000;Vought et al 1995), achieved following rehabilitation of riparian ecotones (Mander et al 1995;Robertson and Rowling 2000;Vought et al 1995).…”
Section: Introductionmentioning
confidence: 99%